EFEKTIFITAS PERMAINAN SCRABBLE DALAM MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN BAGI ANAK KESULITAN MEMBACA - Nadya Yualdi, Ganda Sumekar, Tarmansyah (Universitas Negeri Padang, 2013)
The research was background by the problems that researchers found that a child in third grade elementary school of SDN 20 Padang Binuang. Children have difficulty in reading. The type of research is experimental research in the form of single subject reseach (SSR) using ABA design and data analysis techniques using visual analysis chart. Result of this study show that reading skills of children with reading difficulties increase by scrabble game. It is recommended that teachers use the scrabble game in teaching children to read.